Article title: Mean-Variance model : Added value of family business stocks. - Mounir, Amine (IJRDO - Journal of Applied Management Science, 2017)
Family business performance has been widely explored in the literature from corporateperspective. An open question is how individual investors can benefit from this performance inreturn-risk portfolio investment setting. This paper investigates the benefit of diversificationusing family business stocks in financial portfolios. Based on the geometric representation ofthe minimum variance frontier and asymptotic spanning tests, this paper highlights theimportant role of family business stocks in risk contraction in diversified financial portfolios.